2022
DOI: 10.1007/s12015-021-10261-4
|View full text |Cite
|
Sign up to set email alerts
|

Extracellular Vesicles of Mesenchymal Stromal Cells Can be Taken Up by Microglial Cells and Partially Prevent the Stimulation Induced by β-amyloid

Abstract: Mesenchymal stromal/stem cells (MSCs) have great capacity for immune regulation. MSCs provide protective paracrine effects, which are partially exerted by extracellular vesicles (EVs). It has been reported that MSCs-derived EVs (MSC-EVs) contain soluble factors, such as cytokines, chemokines, growth factors and even microRNAs, which confer them similar anti-inflammatory and regenerative effects to MSCs. Moreover, MSCs modulate microglia activation through a dual mechanism of action that relies both on cell con… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 55 publications
0
10
0
Order By: Relevance
“…Mesenchymal stem cells (MSC) possess immunomodulatory and tissue regenerative properties and, therefore, have been suggested as therapeutic tools ( Pittenger et al, 2019 ). MSC-derived exosomes have been shown to decrease Aβ levels but also inhibit the Aβ-driven downregulation of synaptic plasticity-related genes ( Chen et al, 2021 ) or microglial activation ( Kaniowska et al, 2022 ). Other studies have also shown that MSC-derived EVs have beneficial effects in in vitro AD models by protecting neurons from oxidative stress and synaptic damage induced by Aβ oligomers ( Bodart-Santos et al, 2019 ; de Godoy et al, 2018 ).…”
Section: Evs As Ad Drug Targets and Therapy Delivery Systemsmentioning
confidence: 99%
“…Mesenchymal stem cells (MSC) possess immunomodulatory and tissue regenerative properties and, therefore, have been suggested as therapeutic tools ( Pittenger et al, 2019 ). MSC-derived exosomes have been shown to decrease Aβ levels but also inhibit the Aβ-driven downregulation of synaptic plasticity-related genes ( Chen et al, 2021 ) or microglial activation ( Kaniowska et al, 2022 ). Other studies have also shown that MSC-derived EVs have beneficial effects in in vitro AD models by protecting neurons from oxidative stress and synaptic damage induced by Aβ oligomers ( Bodart-Santos et al, 2019 ; de Godoy et al, 2018 ).…”
Section: Evs As Ad Drug Targets and Therapy Delivery Systemsmentioning
confidence: 99%
“…Our novel microglia modulation assay provides a neuroinflammation-relevant context for assessing MSC-EVs from different priming conditions. MSC-EV modulation of microglia has been explored both in vitro and in vivo : ADMSC-EVs significantly decreased TNF-α secretion by microglia stimulated with lipopolysaccharide (LPS) or amyloid-beta (Aβ), a hallmark peptide of Alzheimer's disease [ 123 ]. In a triple transgenic mouse model of Alzheimer's disease, IFN-γ/TNF-α primed MSC-EVs delivered intranasally reduced microglia Iba-1 and CD68 (activation markers) expression and soma size, signifying an overall suppression of microglia activation [ 124 ].…”
Section: Discussionmentioning
confidence: 99%
“…Our novel microglia modulation assay provides a neuroinflammation-relevant context for assessing MSC-EVs from different priming conditions. MSC-EV modulation of microglia has been explored both in vitro and in vivo : ADMSC-EVs significantly decreased TNF-α secretion by microglia stimulated with LPS or amyloid-beta (Aβ), a hallmark peptide of Alzheimer’s Disease (122). In a triple transgenic mouse model of Alzheimer’s Disease, IFN-γ/TNF-α primed MSC-EVs delivered intranasally reduced microglia Iba-1 and CD68 (activation markers) expression and soma size, signifying an overall suppression of microglia activation (123).…”
Section: Discussionmentioning
confidence: 99%